APPLICATION OF ARTIFICIAL INTELLIGENCE IN MODERN WARFARE - Miljković, Milan Đ; Beriša, Hatidža (The Policy of National Security, 2023)
Artificial intelligence is making rapid strides, and trying to predict its limits is an uncertain endeavor. While it opens up significant opportunities, it also presents challenges. AI has the potential to greatly enhance military capabilities, acting as a force multiplier. Military applications of AI can confer a competitive edge by expediting decision-making, revolutionizing the decision-making process, and improving command, control, and oversight capabilities. Similar to any groundbreaking technology, AI is poised to spark competition among powerful nations, potentially giving rise to security dilemmas, disrupting conflict predictability, and increasing the risk of escalation.At its core, the pivotal question centers on the interaction between human operators and AI systems. In the realm of strategy, official state documents underscore the strategic significance of AI development and deployment in military endeavors. AI systems are likely to bolster military strategy, especially in forecasting and planning. Nevertheless, the human element in shaping strategy remains paramount, as it relies on instincts, creativity, and values. Nonetheless, there remains a concern that military personnel might excessively rely on AI for decision-making. In terms of military doctrine, the role of AI will likely be limited to assessment and aiding in doctrine revision. Considering that doctrine outlines a state's armed forces' purpose, values, and organizational culture, it is apparent that doctrine will play a pivotal role in defining how a state's military perceives and interacts with AI systems.Artificial intelligence will play a substantial role in military planning, primarily due to its capacity to rapidly and accurately process complex and vast datasets. Even if AI systems are not granted decision-making authority, military planners and commanders may heavily depend on AI analyses and recommendations due to time constraints and the intricacies of wartime scenarios. Consequently, the line between AI that supports decision-making and AI that makes decisions itself could become less distinct. Concerning Rules of Engagement, they serve as a suitable framework for distinguishing the utilization of AI in specific conflicts and missions. In the realm of military orders, AI systems are expected to offer significant support in command and control functions, though they may not be entrusted with issuing orders independently. Nevertheless, practical challenges may arise in distinguishing between orders issued by algorithms and those given by commanders, potentially resulting in de facto AI-driven decision-making, akin to the planning stage.Military structures, standards, and processes are likely to adapt in tandem with technological advancements. It is, therefore, imperative to proactively establish fundamental principles, values, and standards governing AI use, rather than reacting to technological developments, to avert unforeseen or undesirable consequences.Future discussions and research on AI's role in military operations, as well as its integration into strategy, doctrine, operational plans, Rules of Engagement, and orders, should concentrate on the interaction between humans and machines, as this remains the crux of the matter. Striking an appropriate balance between AI's role in military preparation and execution and the effective management of military artificial intelligence is of paramount importance.
Keywords: Artificial intelligence; strategy; doctrine; military operations; command